Towards a generalist approach in social work practice - Mendoza, Thelma Lee (1997)
Social work practice in Asia has followed the Western model which means the use of the traditional separate methods of social casework, social group work, and community organization. This model, however, has been overtaken by newer ways of viewing social work practice. A major source of influence is social systems theory. In addition, in the case of developing countries, the United Nations' call for a more development-oriented social welfare that is not bound by traditional ways of helping people has led to efforts to improve the content of social work education particularly in the social work practice area. The pursuit of a "generalist approach" in practice is one such effort.
This paper presents a framework for a "generalist approach" in social work. The author contends that a common generic base in social work values and knowledge can and should be taught to social work students.
She presents an outline of what she thinks should comprise this value base and knowledge base that is essential if a "generalist" practitioner is to work with client systems of all "sizes."
Keywords: Social services; Social group work